Chromosome-level genome assembly of Z strain European corn borer Ostrinia nubilalis (Lepidoptera: Crambidae) - Xinhua Ding; Yue Zhang; Xiaowu Wang; Kaiyun Fu; Zunzun Jia; Zhihui Wang; Aerziguli Rouzi; Tursun Ahmat; Wenchao Guo (Scientific Data)
Abstract European corn borer Ostrinia nubilalis (Hübner) is the most important pest of maize around world, and an ideal model for the sympatric host races, evolutionary and speciation research. In this study, we assembled a chromosome-level genome of Z strain O. nubilalis by the integrated Illumina short reads, PacBio Revio long reads, and Hi-C sequencing data. The chromosome-level genome was 480.04 Mb in total length with a contig N50 length of 16.51 Mb, which 98.59% genome anchored into 31 chromosomes. For the annotation, 1,046,695 repeat sequences in length of 212.07 Mb, 1,550 non-coding RNAs (including 1,208 tRNAs, 179 rRNAs, 62 miRNAs, 81 snRNAs, and 20 snoRNAs), and 17,145 protein-coding genes were identified. And 100% genes were functional annotated by SwissProt, NR, eggNOG, Go, and KEGG database. This genome provides a valuable genomics resource to elucidate the host plant adaptation, thermal adaptation, diapause induction, Bacillus thuringiensis toxin resistance, sexual communication, sympatric host races, and speciation process of O. nubilalis.